Angiotensin I Infusion Reveals Differential Effects of Angiotensin-Converting Enzyme in Aortic Resident Cells on Aneurysm Formation - Sawada, Hisashi (Circ J, 2020)
BACKGROUND: Angiotensin (Ang)I is cleaved by angiotensin-converting enzyme (ACE) to generate AngII. The purpose of this study was to determine the roles of ACE in endothelial and smooth muscle cells in aortic aneurysms. METHODS AND RESULTS: AngI infusion led to thoracic and abdominal aortic aneurysms in low-density lipoprotein receptor-deficient mice, which were ablated by ACE inhibition. Endothelial or smooth muscle cell-specific ACE deletion resulted in reduction of AngI-induced thoracic, but not abdominal, aortic dilatation. CONCLUSIONS: AngI infusion causes thoracic and abdominal aortic aneurysms in mice. ACE in aortic resident cells has differential effects on AngI-induced thoracic and abdominal aortic aneurysms.